Analisis Kepatuhan Hukum Masyarakat Kota Tanjung Balai Dalam Memenuhi Syarat-Syarat Mengendarai Sepeda Motor - Siti Nur Diah; Arief Wahyudi (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the legal compliance of the people of Tanjung City in fulfilling the requirements for riding motorbikes, and to find out the factors that cause the people of Tanjung Balai City to not comply with the requirements for riding motorbikes. The type of research carried out is empirical legal research with qualitative research methods. Data collection tools used to obtain data are observation, interviews and documentation. Based on the research results, it is stated that the level of legal compliance among the people of Tanjungbalai City is still relatively low. This is proven by the number of violations which increases every year. The low level of compliance of the people of Tanjungbalai City in fulfilling the requirements for riding a motorbike is caused by several factors. These causal factors include the low level of public education resulting in a lack of understanding, lack of legal awareness in the community, and lack of trust in police officers. Most of the people of Tanjungbalai City already have knowledge of the requirements for riding a motorbike but are reluctant to comply because they lack legal awareness. Another cause is a lack of trust in traffic police officers.